Dissatisfaction with the laboratory services in conducting HIV related testing among public and private medical personnel in Tanzania - Mtandu R; Ngowi B; Senkoro M; Kivuyo S; Kilale A; Kimaro G; Kahwa A; Mfinanga SG; Mutayoba B; Ngadaya E; Mashoto K (BMC Health Services Research, 2008)
Abstract Background A comprehensive care and treatment program requires a well functioning laboratory services. We assessed satisfaction of medical personnel to the laboratory services to guide process of quality improvement of the services. Methodology A cross-sectional survey in 24 randomly selected health facilities in Mainland Tanzania was conducted to assess the satisfaction of the medical personnel with the laboratory services. Results Of 235 medical personnel interviewed, 196 were valid for analysis and about one quarter were dissatisfied with the laboratory services. Personnel dissatisfied with the services were 38.3% in timely test result, 24.5% in correct and accurate results and 22.4% in clear complete results. The personnel in public laboratories were more dissatisfied with timely test results (OR = 3.6, 95% CI 1.8, 7.3), correct results (OR = 4.1, 95% CI 1.6, 10.8) and clear complete results (OR = 5.0 95% CI 1.6, 15.2). Personnel dissatisfied with the services in 15 laboratories sending specimens to referral laboratories, varied from 13% in availability of equipment to 57% in timely results feedback from the referral laboratories. Personnel dissatisfied with the services in 14 referral laboratories, varied from 28.6% in properly identified specimen to 42.9% in clear, accurate test request and communication. Conclusion About one quarter of medical personnel in sending or receiving laboratories were dissatisfied with the services. Comparing the personnel in public and private, the personnel in public laboratories were 4 times more dissatisfied with the timely test and correct results; and 5 times more dissatisfied with clear and complete test results.